2022
DOI: 10.1016/j.burns.2021.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Quality improvement training for burn care in low-and middle-income countries: A pilot course for nurses

Abstract: Highlights We can empower practitioners to lead quality improvement projects in LMICs. Nurses can play a significant role in the improvement of burns services. Interactive blended-learning courses can support nurses to lead on quality improvement. The training and development must be designed to be context specific.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Numerous academics have stressed the significance of training in relation to QI. As indicated previously, a negative approach with respect to training was recognised as a main obstacle in implementing a QI initiative (Holden et al, 2021). Training is an instrument that assists a firm to attain its TQM objectives and to adhere to the needs of its clientele (Ajgaonkar et al, 2021).…”
Section: Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous academics have stressed the significance of training in relation to QI. As indicated previously, a negative approach with respect to training was recognised as a main obstacle in implementing a QI initiative (Holden et al, 2021). Training is an instrument that assists a firm to attain its TQM objectives and to adhere to the needs of its clientele (Ajgaonkar et al, 2021).…”
Section: Trainingmentioning
confidence: 99%
“…Moreover, additional education with the objective of acquiring more aptitudes and knowledge should be put in place in order to facilitate successful QI instigation. In burn services in Malawi and Ethiopia, in relation to QI initiatives, major enablers included efficacious KS, whereas a negative ethos with respect to training was a main obstacle (Holden et al ., 2021). Through a literature review of health professions education, KS was found to be an important factor affecting QI (Matinho et al ., 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Holden et al demonstrated the effectiveness of providing an online forum in order to help nurses in Malawi and Ethiopia more collaboratively develop quality improvement campaigns for burn victims. 58 Connecting plastic surgery residents with experts and peers from around the globe can be a useful way to share knowledge and establish networks through open dialogue. This form of global education is already taking root, particularly due to COVID-19.…”
Section: The Roadmap Forwardmentioning
confidence: 99%
“…As nursing students are at the frontline of caring for burned patients, they are indispensable in the multidisciplinary burn care team. In addition to carrying out routine care and specialized burn care for patients as drainage tube care, scar physiotherapy, wound care (Holden et al, 2022). Nursing students undertaking clinical training at a burn unit in which they get sufficient knowledge about the physiological effects of burns and be able to quickly analyze and make decisions regarding minor changes in patient status.…”
Section: Introductionmentioning
confidence: 99%